Corporate Reputation, Available Slack, And Financial Distress Risk - Aminatuzzuhro; Indrawati, Trisa; Fitriani, Nurul (Jurnal Akuntansi, 2024)
The global COVID-19 pandemic and the associated economic recession have posed significant challenges for companies in Indonesia. Many companies have struggled to survive, leading to mass layoffs or bankruptcy. This study is motivated to research the financial factors (namely, company reputation and available slack) related to the risk of financial difficulties, using 1,699 observations from non-financial public companies in Indonesia from 2020 to 2022. The research was conducted using moderated regression analysis performed with STATA software. The research results indicate that company reputation is negatively related to the risk of financial difficulties, and available slack strengthens this relationship. These results were robustly tested using coarsened exact matching. This study provides information for companies and stakeholders on reducing the risk of financial difficulties by strengthening the company's reputation and available slack.